2017
DOI: 10.1051/e3sconf/20171700044
|View full text |Cite
|
Sign up to set email alerts
|

Application of nanofiltration membranes for removal of surfactants from water solutions

Abstract: Abstract. The objective of the study was to compare effectiveness of nanofiltration (NF) process for treatment aqueous solutions containing various types of surfactants (anionic, cationic and non-ionic). The experiments were conducted with the use of Microdyn-Nadir ® nanofiltration membranes (NP010 and NP030). The effect of surfactant type, its concentration and membrane cut-off on the process parameters (retention coefficient and permeate flux) was assessed. The experiments showed that separation of anionic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Various methods have been developed to remove LAS surfactant in water and wastewater, such as adsorption [3][4], coagulation [2,[5][6], and filtration [7][8]. By adsorption, coagulation, and filtration techniques, the surfactant of LAS is only replaced from water to the adsorbents, coagulants and membranes with the same toxicity [1], then they are collected as hazardous solid wastes.…”
Section: The Laundry Wastewater Treatment Methodsmentioning
confidence: 99%
“…Various methods have been developed to remove LAS surfactant in water and wastewater, such as adsorption [3][4], coagulation [2,[5][6], and filtration [7][8]. By adsorption, coagulation, and filtration techniques, the surfactant of LAS is only replaced from water to the adsorbents, coagulants and membranes with the same toxicity [1], then they are collected as hazardous solid wastes.…”
Section: The Laundry Wastewater Treatment Methodsmentioning
confidence: 99%
“…The fouling mechanisms, including concentration polarization, gel layer formation, and pore blocking, introduce additional resistance during the transport through the membrane due to increased osmotic pressure on the feed side [13,26]. Kowalska and Klimonda [19] showed that the surfactant concentration in the solution is the key parameter that has a significant influence on the separation performance. Increasing the dose of surfactant in the feed results in deterioration of the membrane permeability and strongly affects its separation properties [19].…”
Section: Nanofiltrationmentioning
confidence: 99%
“…The experimental results demonstrated that the concentration of the surfactant in the solution was the key parameter that significantly affected the process performance. Increasing the amount of surfactant in the feed impaired the permeability of the membranes and strongly affected their separation properties, which differed significantly at different concentrations [19].…”
Section: Nanofiltrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrafiltration membranes with a molecular weight cut-off (MWCO) of 5-10 kDa are suitable to filter micelles [21,23,24]. Nanofiltration membranes (WMCO < 1 kDa) can also be applied for this step [25]. The major drawback of MEUF is the flux through the membrane that defines the total separation time.…”
Section: Micellar Enhanced Ultrafiltrationmentioning
confidence: 99%